2015
DOI: 10.1021/acsami.5b06825
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stable and Tunable Chemical Doping of Multilayer WS2 Field Effect Transistor: Reduction in Contact Resistance

Abstract: The development of low resistance contacts to 2D transition-metal dichalcogenides (TMDs) is still a big challenge for the future generation field effect transistors (FETs) and optoelectronic devices. Here, we report a chemical doping technique to achieve low contact resistance by keeping the intrinsic properties of few layers WS2. The transfer length method has been used to investigate the effect of chemical doping on contact resistance. After doping, the contact resistance (Rc) of multilayer (ML) WS2 has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
84
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 135 publications
(95 citation statements)
references
References 40 publications
3
84
0
Order By: Relevance
“…The ions with different electron affinity can act as electron donors and acceptors. Khalil et al reported the doping of WS 2 by LiF . The F − ions has extra electrons.…”
Section: Doping Engineeringmentioning
confidence: 99%
“…The ions with different electron affinity can act as electron donors and acceptors. Khalil et al reported the doping of WS 2 by LiF . The F − ions has extra electrons.…”
Section: Doping Engineeringmentioning
confidence: 99%
“…The electronic and optical properties of unipolar n‐type WS 2 can also be manipulated by the SCTD method. Khalil et al reported a downshift of the Raman peak for WS 2 by using LiF as an n‐type dopant . The light emission of WS 2 could be remarkably enhanced after the decoration of F4‐TCNQ molecules, due to the depletion of electrons in the WS 2 upon doping .…”
Section: Sctd In 2d Nanostructuresmentioning
confidence: 99%
“…8,9 In particular, during the last few years intense attention has been given to the broad and versatile group of transition metal dichalcogenides (TMDCs), which includes metals and semimetals as well as semiconductors with band gaps varying from less than 1 to nearly 3 eV. 2,3,10,11 The properties of TMDCs can be further tailored by controlling their thickness, 12,13 surface functionalization, 14 strain, 15,16 doping and alloying, 17,18 and creating heterostructures with other 2D materials. 8,17,19 Tungsten disulfide (WS2) is a semiconducting TMDC, which has an indirect band gap of 1.3-1.4 eV in bulk in the common 2H and 3R phases, which have trigonal prismatic coordination around tungsten and only differ in the stacking of the WS2 layers.…”
Section: Introductionmentioning
confidence: 99%